Essays on international transmission of monetary policy and global financial risk spillover - Liu, Jingting (Nanyang Technological University, 2022)
This thesis explores international transmission of monetary policy and global financial risk spillover into emerging market economies in three aspects. First, it asks how US monetary shocks and global financial risks are transmitted into emerging countries by investigating the underlying mechanism and how uncovered interest rate parity (UIP) deviation may be part of the mechanism. Second, it further asks how heterogeneity in country characteristics may lead to variations in periphery advanced and emerging countries’ interest rate, output and credit supply responses following contractionary US monetary spillover. Exposure to dollar debt and financial openness are the two main country characteristics of focus. Third, taking heterogeneity in country characteristics into account, the thesis examines the differences in impact of US monetary spillovers and optimal monetary policy responses for emerging countries with risky and safe banks in a dynamic stochastic general equilibrium (DSGE) model. These three aspects are addressed in detail in the three main chapters (Chapters 2 – 4) comprising the thesis. As the leading chapter, Chapter 1 discusses motivation for the thesis and highlights key contributions of each chapter. It also discusses dominant currency, global financial cycles, the debate on the validity of Mundell-Fleming Trilemma and related issues in international macroeconomics. Chapter 2 studies the impact and transmission mechanism of US monetary and global financial risk spillover into emerging countries using panel VAR. It finds that one standard deviation increase in the US interest rate reduces output and investment in emerging countries by 0.1% and 1%. These variables drop by 0.5% and 1.8% following a global financial risk (proxied by CBOE Volatility Index, or VIX) shock. The chapter provides evidence that global financial risk spillover and US monetary shock transmission into emerging countries is at least partly through movement in UIP deviation. In fact, global financial risk (VIX) and UIP deviation are highly correlated: High global financial risk (VIX) is often accompanied by high UIP deviation. In a counterfactual analysis, by muting the response of UIP deviation to VIX, negative impact on emerging countries’ GDP due to global financial risk shock is slashed by half. In terms of US monetary spillover, an increase in the US interest rate reduces the UIP deviation of emerging countries on impact because emerging countries’ domestic interest rate responds by less than the US rate. This initial more muted increase in emerging countries’ interest rate is due to an initial drop in the VIX response. In other words, global financial risk proxied by VIX does not increase immediately following contractionary US monetary shocks. Over time, however, the VIX picks up and emerging countries enter a risk-off phase in which credit inflows drop and UIP deviation increases in emerging economies. As part of the chapter’s contribution, this mechanism can also explain Engel’s predictability reversal puzzle as it creates a positive correlation between UIP deviation and the initial period interest rate differential between the emerging country and the US in the short term while in the longer term, this correlation reverses sign. Chapter 3 studies how country heterogeneities, especially in their (1) net exposure to dollar and dollar debt and (2) financial openness affect the propagation of US monetary shocks into peripheral advanced and emerging economies. This chapter contributes to the understanding of how interest rate and GDP responses of emerging countries depend on both their dollar liability and financial openness, as well as the interaction between these two factors. Specifically, the chapter finds that countries that are more net short in dollar have higher interest rate responses, but less so if their financial openness is high. The result suggests the more an economy borrows in dollar the more (less) it may increase (lower) interest rate to reduce negative balance sheet effects, but if its financial openness is high, it may increase (reduce) the interest rate by less (more) to avoid over-contracting its domestic monetary condition which has possibly been tightened due to contractionary US monetary spillover. The chapter also finds that GDP decreases by more for countries that are net borrowers of dollar if their financial openness is high. Using capital control as the de jure measure of financial openness, similar results are obtained that GDP decreases by more for countries that are net borrowers of dollar if capital control is low, and at the same time, GDP is higher for countries with higher capital control if their net dollar external liability is higher. Combined, the results imply that capital control helps dampen the negative US monetary spillover effect on peripheral countries’ real economy, and the benefit from imposing capital control is larger for countries that are more indebted in dollar. Chapter 4 explores the differences in the impact of US monetary spillovers into emerging countries with safe banks and emerging countries with risky banks, and the respective implications for optimal monetary policy making. By constructing a new banking sector risk index, the chapter first provides empirical evidence that banking sector risk can be an important factor amplifying the negative impact on emerging countries’ real economy and financial market due to US monetary shocks using local projection techniques. The chapter finds that emerging countries with riskier banks experience larger drop in output and stock market price even after controlling for other risk factors that include dollar peg, trade integration with US, inflation and external liability position, which is a new result in the chapter. A two-country DSGE model is then developed with financial frictions in both the US and the emerging country that can help to account for the empirical findings. The model incorporates a new modelling feature that when investing in emerging market economies (EMEs) with riskier banks, US investors face a tighter financing constraint, thus require a higher return from the EME in the deterministic steady state. The model simulated impulse responses show that EMEs with riskier banks experience larger output drop, more capital outflow, steeper asset price decline and larger currency depreciation following an unexpected US monetary policy rate increase, and exchange rate stabilizing monetary policies tend to exacerbate welfare losses. For EMEs with safe banks, however, fixed exchange rate policy can outperform inflation targeting policies. Finally, Chapter 5 concludes and discusses how we will extend the research.